Project time, cost and quality constraints management through structured fuzzy mapping on psychological phenomena - Mo, Yiyi; Wang, Chen; Tang, Yutong; Yap, Jeffrey Boon Hui; Wood, Lincoln C.; Guaz, Zhi Wee (Journal of Civil Engineering and Management, 2023)
Construction business involves people from different employers who have to work together in one project, thus a project manager needs to apply scientific principles to understand and to utilize those common psychological phenomena such as Hedgehog Effect, Butterfly Effect, Pygmalion Effect, Boiled Frog Syndrome, Parkinson’s Law, and Bandwagon Effect in completing work well and keeping people satisfied. The aim of this study is to develop a fuzzy mapping to assist project managers in implementing significant psychological phenomena in construction management through reflections on common psychological phenomena in the construction management. Through a structured interview survey among construction managers, the inferential association among gender, working experience, and the six psychological phenomena were plotted based on the Partial Least Square Structural Equation Modelling. Through the pairwise comparison technique, a fuzzy mapping of psychological phenomena in time, cost, and quality management was developed to facilitate the managerial efficiency in construction.